The Impact of Physiotherapy on Post-Surgical Rehabilitation Outcomes: A comprehensive review - Maryam Yosif Almodiny,; Basmah Magbal Saleh Alharbi,; Aisha Saud Rabeei Alshammari,; Fahad Abdulazizi Zaid Al Shammri,; Salma Mohammed Alenazi,; Thuraya Radhi Alshammry, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Physical therapy after surgery is a critical stage in the treatment course of patients who have gone through surgeries. This rehabilitation phase is highly determinant of the patient’s recovery, functionality, and quality of life. Among such supportive interventions, Physiotherapy appears to be one of the most useful tools in redesigning the quality of patients’ lives as well as outcomes of the surgeries done. Physiotherapy comprises of diverse approaches like exercises, manipulation techniques and instructions with an aim of eradicating complications on physical mobility after surgery. Aim of work: To explore the multifaceted impact of physiotherapy on post-surgical rehabilitation outcomes, examining its contributions to physical recovery, psychological well-being, prevention of complications, and long-term functionality. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Impact, Physiotherapy, Post-Surgical, Rehabilitation, Outcomes. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Physiotherapy does not limit itself to the physical recovery of patients after surgery as it goes along the way of improving the recovery process by addressing pain issues, complications and psychological health. Through adoption of special programs for the patient’s records and the type of surgery to be undergone, physiotherapists enable an all-round rehabilitation process that caters for the short and long term needs of the patient. The result is faster recovery and thus betters functional results, as well as the additional benefit preventing future health problems, which enable patients to regain independency and return to their everyday life. Not simply enhancing physical functions can help the body to recover, physiotherapy is also significant for enhancing the quality of the life of the patient, and it means it is a crucial factor of the rehabilitation process after surgery.